THE INJURY SEVERITY RATE DIFFERENCES IN PASSENGER CARS AND PICK UP TRUCKS RELATED TWO VEHICLE INVOLVED MOTOR VEHICLE CRASHES IN BRITISH COLUMBIA, CANADA - E.B.R. DESAPRIYA (IATSS Research, 2004)
The effect of large vehicle involvement on motor vehicle crash (MVC) rates and severity has long been a concern in MVC analysis literature. Injuries in drivers and occupants are related to several key factors: the mass of the case vehicle and mass of its collision partner and speed of case vehicle and collision partner at the time of the crash. Objective: To evaluate the relative risk of injury occurrence in collisions between picks up trucks (PU) and passenger sedan cars (PS). Methods: Data from the Insurance Corporation of British Columbia (ICBC) crash data base was used to determine MVC rates and injury occurrence. Descriptive characteristics of the injury location and injury type were analyzed comparing the Odds Ratios and chi-squares. Results: PS occupants received more injuries; Odds Ratio was 2.49 (95% confidence interval: 2.15–2.88). Conclusion: Occupants in PS which collide with PU were at twice the risk of injuries. Concussion, whiplash, lacerations and abrasion were more frequent in PS drivers and occupants than in PU drivers and occupants. Overall, PS drivers/occupants experienced greater injuries than PU drivers/occupants in PU-PS collisions. In this paper, results are shown as odds ratios comparing occupants injuries in PS (case group) with occupant injuries in PU (control group).